PENERAPAN SISTEM INFORMASI MANAJEMEN NIKAH (SIMKAH) DALAM PELAYANAN ADMINISTRASI KANTOR URUSAN AGAMA (KUA) KECAMATAN BANGKALA KABUPATEN JENEPONTO - Haris, Andi Hasrul; Suaidah, Idah; Suarga; Kamal, St. Ibrah Mustafa; Baharuddin (Educational Leadership: Jurnal Manajemen Pendidikan, 2025)
This study examines the implementation of the Marriage Management Information System (Simkah) in administration, focusing on the description of its application, challenges, and solutions related to Simkah and administrative services. The methodology used is qualitative with a phenomenological approach, with primary data sources from the Head of KUA, Simkah operators, administrative staff, and service users, as well as secondary data from books and journals. Data were collected through observation, interviews, and documentation, and analyzed through data reduction, presentation, and conclusion drawing. The results indicate that although Simkah faces challenges such as signal disruptions and a lack of public understanding, administrative services received a positive response. Proposed solutions include system updates and staff training. The study also found that factors hindering the implementation of Simkah include insufficient socialization by law enforcement and server instability